Upaya Pengendalian Kebiasaan Jajan Pada Anak Di PAUD Arsari - Harisoesyanti, Kania Saraswati; Machdum, Sari Viciawati (Jurnal Ilmu Kesejahteraan Sosial, 2014)
As an educational institution, PAUD can provides protection and serves as an educational institution that support student health. This role is inseparable from the role of educators, including tutors roles at PAUD Arsari located in North Jakarta. The purpose of this study was to describe PAUD Arsari’s effort in controlling student’s buying habit and to describe barriers experienced by PAUD Arsari’s in an attempt to control students’ buying habit. Using qualitative research approach, data collection was conducted by literature study, interviews and observation. Based on the findings, PAUD Arsari have some policies and implementation methods in controlling students’ buying habit. PAUD Arsari realize that these efforts can support students’ growth and developmet.